Investigation of oil burner combustion performance when utilizing palm biodiesel blends - Muhammad Azreen Azeem, Hasagaya; Mohammad Nazri, Mohd Jaafar; Mohamad Shaiful Ashrul, Ishak (Praise Worthy Prize S.r.l, 2013)
Link to publisher's homepage at http://www.praiseworthyprize.com/